Effects of half- vs three-quarterseason grazing of native grass pastures - Brazle, F.K.; Kilgore, Gary L.; Fausett, M.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Mixed-breed steers (563 lbs) grazed burned, native-grass pastures (1990 to 1998). Steers were allotted randomly to graze native grass pastures for either 1/2 season (1/2) from April to July 15 (81 days, at 1 steer to 2 acres) or for 3/4 season (3/4) from April to August 15 (112 days, at 1 steer per 3 acres). The grass composition was measured in the first, fourth, and eighth years of the study. The economics of steers grazing the two systems were determined by calf and feeder cattle prices at Dodge City adjusted to southeast Kansas. The steers grazing 1/2 gained more per day (2.78 lb vs 2.48 lb, P<.01) but gained less (P<.01) per season (225 lb vs 278 lb). No changes in percentage composition occurred between systems for big bluestem, little bluestem, switchgrass, total perennial grass, or total perennial forbs. However, Indiangrass increased more (P<.05) while managed under 1/2 than 3/4 grazing. The 1/2 system had a higher return per acre, but the 3/4 system had a higher return per head. Grazing system did not appear to have a negative effect on grass composition during the 9-year period.
Keywords: Beef; Native grass; Stocker cattle; Grazing systems